The Improvement of Student’s Critical Thinking Skills Through the Development of Science Learning Material Based Socioscientific Issues with Interactive Multimedia-Assisted on Gadget - Ayu Ilfiana; Wahono Widodo; Pirim Setiarso (Postgraduate, University of Mataram, 2021)
This research aims at understanding the effect of Socioscientific Issues (SSI)-based interactive multimedia (MMI) on the gadget (MMI-SSI-GADGET) toward the junior high school student’s critical thinking skills. The research was conducted in two stages. The first stage was the preparation, which was done to design the learning tools. The next stage was the teaching and learning process in the classroom using pre-test post-test design. The subjects of the research were 28 students of class VII A3 at MTsN 3 Trenggalek. The results of this research showed that the validity score for the learning tools was 3.84 with a percentage of 98.04%, which was categorized as very valid. The practicality percentage was 88.5% which was categorized as very practical, and the N-gain effectiveness was 0,77, which was categorized as very good. Based on the data analysis, it can be concluded that SSI-based MMI on gadgets was categorized as 'very suitable' to improve the junior high school students' critical thinking